EKSISTENSI ISLAM KULTURAL DI TENGAH GEMPURAN GERAKAN ISLAM TRANSNASIONAL - Ahmad Syarif Hidayatullah (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2018)
In the midst of the swift flow of transnational Islamic movements in spreading the ideas and ideologies of puritanism to all levels of Indonesian society that not only to the urban community but also has penetrated into the corners of the village at least it has led to resistance from the Muslim community of Indonesia, especially the Muslim community strongly upholding traditional values ​​in their religious systems. Such resistance is seen in some cases that occur on the island of Bangka which is related to the culture of maulidan, grave, tahlilan, and the reading of talqin which has become a tradition of Muslim communities of Bangka island. However, responding and responding to this, Kampung teachers using and promoting the method of education and teaching 'pengajian kampung' at least enough to stem the flow of movement of ideology of puritanism that began to penetrate into the island community of Bangka. So then the existence of Islamic cultural that characteristic of Malay can still be maintained.